TEXTUAL NOTES ON PINDAR'S ELEVENTH NEMEAN. (December 2020) - Lane, Nicholas
Abstract : εἰ δέ τιϲ ὄλβον ἔχων μορφᾷ παραμεύϲεται ἄλλουϲ, ἔν τ᾽ ἀέθλοιϲιν ἀριϲτεύων ἐπέδειξεν βίαν, θνατὰ μεμνάϲθω περιϲτέλλων μέλη, 15 καὶ τελευτὰν ἁπάντων γᾶν ἐπιεϲϲόμενοϲ. ἐν λόγοιϲ δ᾽ ἀϲτῶν ἀγαθοῖϲί νιν αἰνεῖϲθαι χρεὼν καὶ μελιγδούποιϲι δαιδαλθέντα μελίζεν ἀοιδαῖϲ. The Loeb translates lines 15–16 ʻlet him remember that mortal are the limbs he clothes and that earth is the last garment of all he will wear'. It is debatable whether τελευτάν is an adverbial accusative with ἁπάντων added as a qualifying genitive, as it seems more natural to take the phrase as a simple apposition to γᾶν. But there is a real difficulty in that τελευτὰν ἁπάντων could be taken to indicate that death is 'the end of everything' (or ʻof all men') and that contradicts indications elsewhere in Pindar that death is not, or at least not quite, the end.